2006
DOI: 10.1007/s00223-005-0170-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study on Osteoconductivity by Synthetic Octacalcium Phosphate and Sintered Hydroxyapatite in Rabbit Bone Marrow

Abstract: Octacalcium phosphate (OCP) is thought to be a precursor of the mineral crystals in biological apatite. Synthetic OCP has been shown to be converted into an apatite structure when implanted in murine calvarial bone, to enhance bone regeneration more than synthetic hydroxyapatite (HA), and to degrade faster than biodegradable beta-tricalcium phosphate. This study was designed to investigate whether OCP implantation enhances the formation and resorption of new bone (remodeling) concomitant with OCP degradation w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
118
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(144 citation statements)
references
References 48 publications
7
118
0
3
Order By: Relevance
“…The present study did not provide complete explanation for the adverse effects of the calcium concentration on ST-2 cells. However, the tendency to reduce calcium concentration by OCP surely reflects the in vivo observation that host osteoblastic cells are stimulated by OCP if implanted in bone defects as reported previously 13,48,49) . Pi ions have been found to play multiple roles in maintaining osteoblast-like cells 18) .…”
Section: Discussionsupporting
confidence: 66%
“…The present study did not provide complete explanation for the adverse effects of the calcium concentration on ST-2 cells. However, the tendency to reduce calcium concentration by OCP surely reflects the in vivo observation that host osteoblastic cells are stimulated by OCP if implanted in bone defects as reported previously 13,48,49) . Pi ions have been found to play multiple roles in maintaining osteoblast-like cells 18) .…”
Section: Discussionsupporting
confidence: 66%
“…In these experiments, HHA was biodegradable in implanted bone tissue, and higher MAR in specimens implanted with HHA might be associated with osteoclastic resorption of HHA. Biphagic calcium phosphate and octacalcium phosphate have also been shown to be resorbed by osteoclasts [20,21]. In addition, it was shown that the amount of newly formed bone in the region implanted with biphagic calcium phosphate or octacalcium phosphate is more than that of HA using animal models [12,22].…”
Section: Introductionmentioning
confidence: 99%
“…Исследования in vivo показали, что синтетический ОКФ в мышечных (S. Ban и соавт., 1992), подкожных [20] тканях и на различных костных участках [10,19,20] превращается в биологический апатит. Также было показано, что вслед за резорбцией ОКФ происходит его замещение новой костью [8,10]. Кроме того, было обна-ружено, что покрытие ОКФ на дентальных имплантатах способствует активной остеоинтеграции [4,5], стимулирует пролиферацию остеобластных клеток [6], а в ряде случаев способствует эктопическому остеогенезу [7,21].…”
Section: стоматология 3 2016unclassified